Pathological alleles of MPV17 modeled in the yeast Saccharomyces cerevisiae orthologous gene SYM1 reveal their inability to take part in a high molecular weight complex - Gilberti, Micol (PLoS One, 2018)
Mitochondrial DNA depletion syndromes (MDDS) are a genetically and clinically heterogeneous group of human diseases caused by mutations in nuclear genes and characterized by a severe reduction in mitochondrial DNA (mtDNA) copy number leading to impaired energy production in affected tissues and organs. Mutations in the MPV17 gene, whose role is still elusive, were described as cause of the hepatocerebral form of MDDS and Navajo neuro-hepathopathy. The high degree of conservation observed between MPV17 and its yeast homolog SYM1 made the latter a good model for the study of the pathology. Here, we used Saccharomyces cerevisiae to elucidate the molecular consequences of seven MPV17 missense mutations identified in patients and localized in different protein domains. The phenotypic analysis of the appropriate sym1 mutant strains created demonstrated deleterious effect for all mutations regarding OXPHOS metabolism and mtDNA stability. We deepened the pathogenic effect of the mutations by investigating whether they prevented the correct protein localization into the mitochondria or affected the stability of the proteins. All the Sym1 mutant proteins correctly localized into the mitochondria and only one mutation predominantly affects protein stability. All the other mutations compromised the formation of the high molecular weight complex of unknown composition, previously identified both in yeast, cell cultures and mouse tissues, as demonstrated by the consistent fraction of the Sym1 mutant proteins found free or in not fully assembled complex, strengthening its role as protein forming part of a high molecular weight complex.